Valleien van Samber en Leie - Augustyn, Beatrijs, 1952-2013; Berger, Roger, 1969-; Culot, Paul, 1931-2017; Duvosquel, Jean-Marie, 1946- (Brussel : Gemeentekrediet van België, 1989)
Beschrijvingen van de plaatsen: Bois du Nouvion - Le Favril - Landrecies - Mormal - Noyelles - Sassegnies - Berlaimont - Aulnoye - Aymeries - Pont-s -S - - Bachant - Boussières-s-S - Saint-Rémy-du-Nord - Hautmont - Maubeuge - Assevent - Recquiqnies - Boussois - Rocq - Marpent - Jeumont - Erquelinnes - Solre-s-S - Thuin - Hourpes - Châtelet - Châtelineau - Farciennes - Pont-de-Loup - Tergnée - Moignelée - Oignies - Aiseau - Tamines - Auvelais - Jemeppe-s-S - Moustier-s-S - Ham-s-S - Mornimont - Franière - Soye - Floreffe - Floriffoux - Malonne - Flawinne - Salzinnes - Namen - Lisbourg - Verchin - Lugy - Hézecques - Matringhem - Vincly - Dennebroeucq - Capelle-s-L - Coyecques - Delettes - Nielles - Théroanne - Clarques - Crecques - Rebecques - Thiennes - Haverskerque - Merville - Beaupré - La Gorgue - Estaires - Sailly-s-L - Erquinhem-s-L - Armentières - Comines - Bousbecque - Halluin - Lauwe - Marke - Kortrijk - Harelbeke - Zulte - Wakken - Oeselgem - Olsene - Gottem - Machelen - Petegem-a-d-L - Grammene - Deinze - Astene - Wallebeke - Ooidonk - Sint-Marie-Leerne - Bachte-Maria-Leene - Sint-Martens-Leerne - Baarle - Drongen, Sint-Marens-Latem - Gent